2012
DOI: 10.1160/th12-01-0010
|View full text |Cite
|
Sign up to set email alerts
|

A nation-wide analysis of venous thromboembolism in 497,180 cancer patients with the development and validation of a risk-stratification scoring system

Abstract: The Asian population is thought to have a low risk of venous thromboembolism (VTE), but the epidemiology of VTE in cancer patients remains unclear. The National Health Insurance Research Database of Taiwan was used to find hospitalised patients newly-diagnosed with cancer to determine the incidence of VTE in cancer patients and to identify the risk factors for VTE. Between 1997 and 2005, 497,180 cancer patients were identified. During a median follow-up of 21.3 months (range 0-119.9 months), 5,296 patients dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 49 publications
4
38
0
1
Order By: Relevance
“…Lower limit of 95% CI of the OR was almost over 1.0 in a combination of non-increased PIC with increased TAT (OR, 2.6; 95% CI, 1.0–6.6; P  = 0.082) by univariate analysis. Table 3 shows VTE prevalence of a high- and low-risk group based on tumor subtypes [6, 18]. The absolute rates of the high- and low-risk group were 38% and 25%, respectively, which is not a significant difference.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower limit of 95% CI of the OR was almost over 1.0 in a combination of non-increased PIC with increased TAT (OR, 2.6; 95% CI, 1.0–6.6; P  = 0.082) by univariate analysis. Table 3 shows VTE prevalence of a high- and low-risk group based on tumor subtypes [6, 18]. The absolute rates of the high- and low-risk group were 38% and 25%, respectively, which is not a significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…of patientsPrevalenceTumor type( n  = 29)( n  = 97)(%)High-risk group for VTE Stomach a 518 Pancreas a 37 Ovary a 13 Lung a 22 Urinary tract a 12 CUP b 14 Sarcoma b 23 Lymphoma a 01 Total154038 c Low-risk group for VTE Colon or rectum626 Breast522 Esophagus36 Biliary tract01 Liver01 Urachus01 Total145725

VTE venous thromboembolism, CUP cancer of unknown primary

a Listed as a risk factor for VTE in National Comprehensive Cancer Network Guidelines 2016 [6]. b Listed as a risk factor for VTE in Asian patients [18]. c Odds ratio was 1.84 vs. low-risk group for VTE (95% confidence interval, 0.8–4.4; P  = 0.25).

…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ethics Review Board of China Medical University granted approval for this study (CMU-REC-101-012). Several Taiwan studies had demonstrated the high accuracy and validity of ICD-9 diagnosis in NHIRD [9,10]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, this study was approved by the Ethics Review Board at China Medical University (CMU-REC-101-012). Several Taiwanese studies had demonstrated the high accuracy and validity of ICD-9 diagnosis in NHIRD [10,11]. …”
Section: Methodsmentioning
confidence: 99%